Lead upwards : how startup joiners can impact new ventures, build amazing careers, and inspire great teams - Brown, Sarah E. (John Wiley & Sons, Inc., 2022)
In Lead Upwards: How Startup Joiners Can Impact New Ventures, Build Amazing Careers, and Inspire Great Teams, startup marketing leader Sarah E. Brown delivers an illuminating and accessible guide to maximizing your impact and delivering results in a startup leadership role. The author draws on over a decade of experience scaling SaaS companies as she explains how to prepare for, earn, and succeed in an executive role at a startup company. The book describes every step on the way to realizing your goals--and the goals of your startup--as you navigate the gap between a management role and the executive team. It covers what to do in your first 90 days, how to build and sustain a healthy team culture, and the art of communicating results to your leadership team and board. You'll also learn: How to manage the challenges posed by leading a remote, distributed, or hybrid team Management strategies based on inclusive and diverse teambuilding, alignment with business objectives, and inspirational leadership Effective ways to level up your skills and stay current as your company grows A must-read book for current and aspiring executives at startup firms, Lead Upwards will also earn a place on the bookshelves of startup board members, founders, funders, and managers seeking a singularly insightful discussion of business leadership.